Optimization of dark chocolate formulation with roasted coriander cake as cocoa substitute - Javad Cheragheshahi; Ali Mohamadi Sani; Elham Mahdian; Sharareh Mohseni; Zahra Nazari (Food Chemistry: X)
Since worldwide demand for cocoa is predicted to exceed supply in the upcoming years, this study aimed to find a substitute for cocoa powder in dark chocolate formulation. In the first phase, Coriander cake, a by-product of extracting oil from coriander seeds, was roasted at 165 °C respectively for 2, 4, 6, 8, and 10 min, and physicochemical characteristics (pH, aw, and color parameters), compositional properties, and total phenolic content were examined and compared to cocoa powder. Coriander cake roasted for 6 min was almost equal to cocoa powder and qualified for use in dark chocolate formulation. In the second phase, roasted coriander cake (RCC) was used as a partial replacement for sugar and cocoa powder. The physicochemical and rheological characteristics of RCC chocolates were evaluated. Appropriate mathematical models defined by using best-fitting analysis described results. According to the results, the fitted models illustrated a desirable coefficient of determination (≥90 %).The optimization of the variables indicated that using RCC 6.08 g, Sugar 14.68 g, and Cocoa 12.23 g produced the optimized RCC chocolate with the highest desirability while maintaining the quality characteristics without undesirable changes. The samples' flow behavior and physicochemical properties showed that RCC could be used as a cocoa substitute.